ERROR ANALYSIS OF SENTENCE STRUCTURE ON STUDENTS' PARAGRAPH WRITING - Endang Setiyo Astuti; Kingkin Puput Kinanti (Jurnal Ilmiah Spectral, 2022)
The objective of this study is to recognize errors in the sentence structure of students' paragraph writing tasks. Quantitative research is applied to find out what type of errors and frequent errors are made by students in writing English paragraphs. There were 20 students' paragraph writing analyzed on the aspect of the verb tenses, subject-verb agreement, articles, pronoun agreement, sentence fragments, and run-on sentences/ comma splices. The result showed that the total for all kinds of errors made by the students in this assignment of paragraph writing was 82 errors. The two frequent errors occur in verb tense (23%) and run-on sentences (27%).